Modality Meanings in Studentâs Argumentative Writing - Surjowati, Ribut (Sebelas Maret University, 2016)
This paper presents some exploratory observations on the use of epistemic and deontic modality in a set of 30 undergraduate studentsâ argumentative writing as classified by Nuyts (2006) and Bybee (1994). It is important to know the studentsâ understanding about when to use these expressions through the use of these epistemic and deontic modality expressions because by acknowledging the studentsâÂ understanding about them, we as a teacher will realize that our students do understand the use of them or they need better perception about modality meanings. Since the way they apply those expressions in their writing reflect their comprehension about the actual use of these expressions in the English language and culture and the indication that the area students need help with. The study finds that in terms of deontic modality, the students used modality auxiliaries more frequently than to the use of lexical verbs, adverbs, adjectives or multi word units to show modality meanings in their writing while in terms of epistemic, they employed multi word units such as I think, to express modality meaning many more compared to other expressions. These findings show that the students do not know precisely the use and meanings of these expressions so that they continually use the similar expressions in their writings or in other words because of their lack information, they ignore the precise use of these expressions. Therefore, there must be more information about the perceptions of modality expressions and the different meanings that these expressions carry.